Evaluasi Pengolahan Sampah Organik Lembaga Pengolahan Sampah (LPS) Kelurahan Air Tawar Timur - Mariza Syahyuda, Nelsy; Irawan, Andi (Riset Sinergi Indonesia, 2022)
Garbage that is disposed of at the Air Cold Disposal Site (TPA) does get treatment upon arrival there. With the sanitary landfill method, inorganic waste is piled up in each different zone. Meanwhile, the collected organic waste is processed into compost. However, as the population of Padang City increases, the amount of waste also increases. In this case, the cold water TPA itself will gradually run out of capacity. From the results of the analysis of the amount of waste generation carried out, it was found that the average amount of waste generated at the Waste Management Institute (LPS) in Air Tawa Timur Village was 1,815.3 kg/day. While the volume accommodated by the Temporary Disposal Site (TPS) is 6,831 m3